2014
DOI: 10.1590/1414-431x20143697
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic concentration of morphine reduces oxidative stress in glioma cell line

Abstract: Morphine is a potent analgesic opioid used extensively for pain treatment. During the last decade, global consumption grew more than 4-fold. However, molecular mechanisms elicited by morphine are not totally understood. Thus, a growing literature indicates that there are additional actions to the analgesic effect. Previous studies about morphine and oxidative stress are controversial and used concentrations outside the range of clinical practice. Therefore, in this study, we hypothesized that a therapeutic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
(46 reference statements)
3
22
0
Order By: Relevance
“…This value is between those previously described for glial cell lines and for primary cultures of astrocytes exposed to MeHg [9] [39] , being closer to the latter value. On the other hand, the morphine concentration used in our work was not cytotoxic to the C6 cell line ( Figure 2 ), in agreement with previous reports showing that even higher concentrations of morphine do not significantly reduce cellular survival in C6 cells [17] , [23] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This value is between those previously described for glial cell lines and for primary cultures of astrocytes exposed to MeHg [9] [39] , being closer to the latter value. On the other hand, the morphine concentration used in our work was not cytotoxic to the C6 cell line ( Figure 2 ), in agreement with previous reports showing that even higher concentrations of morphine do not significantly reduce cellular survival in C6 cells [17] , [23] .…”
Section: Discussionsupporting
confidence: 93%
“…This issue is especially important for drugs used in long-term treatments, such as analgesics. Morphine is one of the most potent analgesics, and possesses a recently demonstrated role in oxidative stress at therapeutic concentrations [17] . Morphine, an opioid, is commonly used to manage moderate to severe pain and is a major option in clinical practice [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Morphine is a strong analgesic opioid which is widely applied for pain reduction in diverse clinical and pathologies condition (e.g., emergencies, cancer, trauma, and assisted ventilation, and the like). High use of this agent can lead to dependence and tolerance (25) and numerous experiments concluded that chronic and acute exposure to morphine can reduce total antioxidant and GSH levels in animal and human liver and brain (26). It was also reported that morphine addiction changes the activity of endogenous antioxidant enzymes such as catalase, glutathione peroxidase, and superoxide dismutase (26).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Almeida et al [162] performed with the use of isolated cells of a C6 glioma exposed to H 2 O 2 and/or morphine for 24 hours, revealed that morphine, administered in standard analgesic doses, may contribute to the minimization of oxidative stress in glia cells. Admittedly, in the cited studies, morphine did not prevent the reduced survivability of cells exposed to H 2 O 2 but did partially prevent lipid peroxidation and did not cause an increase in the level of sulfhydryl groups in the studied cells due to the H 2 O 2 exposure.…”
Section: Alkaloidsmentioning
confidence: 99%
“…The classic analgesic effects of morphine are associated primarily with the activation of µ-receptor, which leads, among other effects, to inhibition of the calcium flow in presynaptic neurons and increased potassium conduction in postsynaptic neurons. Opioid receptors are located in, e.g., glia cells, particularly microglia and astrocytes, where they can participate in, e.g., pathological neurotropism [162]. In embryos of zebrafish (Danio rerio), morphine dosed at 1, 10, or 100 nM increased neuron proliferation, the populations of some neurons, and prevented irregularities in glutamate metabolism in motor and Pax-6 neurons [164].…”
Section: Alkaloidsmentioning
confidence: 99%